DIGITAL MEDIA FOR THE DEVELOPMENT OF BANYU LUMUT TOURISM - Wibowo, Prihandono; Febrianita, Roziana; Hapsari, Renitha Dwi (Global and Policy Journal of International Relations, 2018)
The use of social media for development as well as the promotion of tourism destinations is being loved by the people of Indonesia, both from the government and the private sector. So this paper will explain the same thing a bit. Specifically this article will discuss the development of tourist destinations using one of the social media, namely Instagram. The tourist destinations that we are developing are in the village of Tegaren, District Tugu, Trenggalek Regency. There are three (3) tourist destinations in Tegaren, namely embungs, caves, and waterfalls. The community service that we have done is still focused on one tourist destination, namely embung. The embung in the Tegaren village is called Banyu Lumut. This paper seeks to explain the development of tourist destinations through social media. In this paper, the concept of tourism that is pro-poor tourism, tourism value chain, and productive economic empowerment will be used. The pro-poor tourism approach is used as an alternative step of ecotourism which is expected to be more engaged in labor-intensive development activities rather than capital intensive. The community service that we have done has resulted in the form of an @banyulumut Instagram account which can then be used by the Tegaren village government to promote Tegaren tourism. Keywords: tourism, social media, embung, empowerment, community serviceDOI: https://doi.org/10.33005/jgp.v6i02.1814